Femtosecond Laser Microfabrication of Artificial Compound Eyes - Fan Zhang; Huacheng Xu; Qing Yang; Yu Lu; Guangqing Du; Feng Chen (Photonics, 2024)
Over millions of years of evolution, arthropods have intricately developed and fine-tuned their highly sophisticated compound eye visual systems, serving as a valuable source of inspiration for human emulation and tracking. Femtosecond laser processing technology has attracted attention for its excellent precision, programmable design capabilities, and advanced three-dimensional processing characteristics, especially in the production of artificial bionic compound eye structures, showing unparalleled advantages. This comprehensive review initiates with a succinct introduction to the operational principles of biological compound eyes, providing essential context for the design of biomimetic counterparts. It subsequently offers a concise overview of crucial manufacturing methods for biomimetic compound eye structures. In addition, the application of femtosecond laser technology in the production of biomimetic compound eyes is also briefly introduced. The review concludes by highlighting the current challenges and presenting a forward-looking perspective on the future of this evolving field.